COGNITIVE AND SOCIOLINGUISTIC ASPECTS OF DISCOURSE MARKERS - Shahnoza Ruzieva (Bright Mind Publishing, 2025)
Discourse markers (DMs) serve as essential linguistic tools that not only structure spoken and written discourse but also influence cognitive processing, sociolinguistic interactions, and cross-cultural communication. This study delves into how discourse markers assist in comprehension, memory retention, and social communication, shaping both individual cognition and broader cultural discourse. Through a comparative analysis of English, Uzbek, and Russian, the paper examines how different languages use discourse markers to guide interpretation, signal relationships, and regulate conversational flow. The findings highlight the cognitive significance of DMs in language acquisition, their role in constructing social identity, and their function in pragmatic competence in multilingual contexts. Additionally, the study explores how discourse markers impact digital communication and the adaptation of linguistic structures in globalized environments.
Keywords: Discourse markers, cognitive linguistics, sociolinguistics, pragmatics, multilingual communication, cross-cultural interaction, digital discourse.